(untitled) (Journal of Tourism & Adventure, 2019)
Multi functionality of agriculture in the developed countries is employed as a means of rural revitalization and economic circulation. Although farm diversification in the developing countries is much more crucial, in most of the rural areas of the developing countries, it is not performed, and it is delayed. In this regard, the main objective of this study is to explore the possibilities of the multi functionality of agriculture for the sustainable rural development for the implementation of the sustainable development goals (SDGs) in the developing countries. The empirical study was conducted in two of the rural districts of Nepal called Nuwakot and Rasuwa. The author intentionally chose these districts because it is one separate area north of the capital city Kathmandu and bordering to China. Further, even though the location is nearby the capital city, and the rural villages have excessive potentials for tourism activities, the farmers are still focusing on subsistence farming without getting benefits from tourism. Based on the macro data of Nepal government and field visit, the author conducted a case study. This study explored that most of the household heads are working in the agricultural sector, which can be one of the opportunities to launch multi functionality of agriculture. However, due to their weak educational background, they are expecting external supports in terms of knowledge, technology, and more importantly, supportive policy. The federal and central government should give subsidy to the farmers so that they canstart multi functionality in their farms, which lead to sustainable rural development.